PIONEERING BORNEO TRIZ AND FURTHER PROLIFERATE KNOWLEDGE WITH REMOTE LOCATIONS - Narayanan, Kulathuramaiyer; Rohaya, Mohd Nor; Mohamad Kadim, Suaidi; Awangku Merali, Pengiran Mohamed; Tan, Eng Ho (2023)
TRIZ knowledge has made its way from Russia to many places around the world. It arrived in South East Asia in early 2000 and made great proliferation led by the Malaysia TRIZ community from 2010. With a focused effort to share knowledge, more than 15,000 practitioners were certified in the region over 10 years. Many achievements enjoyed “city” advantage and lacked “rural” comparative support. This paper describes how TRIZ finds its way to Borneo-island. It will document the journey and relate how less-populated locations with limited infrastructure and resources embrace the innovation culture while preserving the traditional tribal way of life. This paper will cover the multifaceted knowledge proliferation and development effort through the pioneering and formation of the Borneo TRIZ commu-nity. It showcases the creativity of the community equipped with TRIZ to solve unique local problems and develop solutions that address challenges of constrained resources.